Sensitivity Analysis of Gear Rattle Parametric of Transmission - Shi Xiaohui; Xiong Xiuwen; Guo Dong; Zheng Guangze; Liu Peihai; Zhang Hailin (Jixie chuandong)
Taking a manual transmission as research object,a simulation analysis model of transmission gear rattle is conducted by using the SIMdrive software,this model considering the influencing factors such as input shaft speed fluctuation,clearance,inertia of loose gear and drag torque,and these influence factors are used to calculate the angular velocity of each loose gear and the engaging force of each idler gear pair. The transmission gear rattle is tested and the loose gear speed signals are measured to verify the effectiveness of the simulation analysis model. From the point of view of the impact energy,the derivative of the idler gear on the meshing force is taken as the rattle index（ Jerk index）,and using the forward difference method to solve the Jerk index under various conditions. The partial derivative of the four parameters of speed fluctuation,clearance,inertia of loose gear and drag torque are obtained respectively,and the sensitivity of each parameter to the transmission gear rattle is obtained. It is found that the sensitivity of the speed fluctuation to the rattle is always positive,and when the speed fluctuates at 40 r/min,the influence on the gear rattle starts to increase sharply.When the clearance is less than 0. 1 mm,the rattle sensitivity is positive,more than 0. 1 mm when the negative.The sensitivity of the inertia of loose gear is always negative,and when the inertia is more than 0. 000 6 kgm2,the rattle sensitivity value is almost unchanged and the effect of the change in inertia on the gear rattle is not noticeable. When the drag torque is less than 0. 6 N·m,the rattle sensitivity is negative,more than 0. 6 N·m when the positive,and at 0. 2 N·m to 0. 3 N·m between the drag torque on the gear rattle is not noticeable.